Water/Ionic Liquid/Succinonitrile Hybrid Electrolytes for Aqueous Batteries. (27th February 2022) - Reber, David; Borodin, Oleg; Becker, Maximilian; Rentsch, Daniel; Thienenkamp, Johannes Helmut; Grissa, Rabeb; Zhao, Wengao; Aribia, Abdessalem; Brunklaus, Gunther; Battaglia, Corsin; Kühnel, Ruben‐Simon
Abstract: The water‐in‐salt concept has significantly improved the electrochemical stability of aqueous electrolytes, and the hybridization with organic solvents or ionic liquids has further enhanced their reductive stability, enabling cell chemistries with up to 150 Wh kg −1 of active material. Here, a large design space is opened by introducing succinonitrile as a cosolvent in water/ionic liquid/succinonitrile hybrid electrolytes (WISHEs). By means of succinonitrile addition, the solubility limits can be fully circumvented, and the properties of the electrolytes can be optimized for various metrics such as highest electrochemical stability, maximum conductivity, or lowest cost. While excessive nitrile fractions render the mixtures flammable, careful selection of component ratios yields highly performant, nonflammable electrolytes that enable stable cycling of Li4 Ti5 O12 –LiNi0.8 Mn0.1 Co0.1 O2 full cells over a wide temperature range with strong rate performance, facilitated by the fast conformational dynamics of succinonitrile. The WISHEs allow stable cycling with a maximum energy density of ≈140 Wh kg −1 of active material, Coulombic efficiencies of close to 99.5% at 1C, and a capacity retention of 53% at 10C relative to 1C. Abstract : Solubility limits of suitable salts hinder the development of water‐in‐salt electrolytes. By introducing cosolvents, these limitations are circumvented and a large design space is opened for non‐flammable, water‐based hybrid electrolytes. Here, succinonitrile is introduced as an electrolyte component, and its fast conformational dynamics is exploited to afford energy‐dense batteries based on Li4 Ti5 O12 and LiNi0.8 Mn0.1 Co0.1 O2 with a strong rate performance over a wide temperature range.